Apsidal alignment in migrating dust - Crescent features caused by eccentric planets. Issue Volume 15:Issue S364(2019) (October 2021) - Sommer, Maximilian; Pokorný, Petr; Yano, Hajime; Srama, Ralf
Abstract: Circumstellar discs are known to exist in great variety, from gas-rich discs around the youngest stars to evolved debris discs such as the solar system's zodiacal cloud. Through gravitational interaction, exoplanets embedded in these discs can generate density variations, imposing potentially observable structural features on the disc such as rings or gaps. Here we report on a mirrored double crescent pattern arising in simulations of discs harbouring a small, moderately eccentric planet - such as Mars. We show that the structure is a result of a directed apsidal precession occurring in particles that migrate the planet's orbital region under Poynting-Robertson drag. We further analyze the strength of this effect with respect to planet and particle parameters.